2001
DOI: 10.1128/jvi.75.22.11034-11055.2001
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Assembly of Intracellular Mature Vaccinia Virus: Isolated-Particle Analysis

Abstract: In a series of papers, we have provided evidence that during its assembly vaccinia virus is enveloped by a membrane cisterna that originates from a specialized, virally modified, smooth-membraned domain of the endoplasmic reticulum ( In this first study, we analyzed the IMV by on-grid staining, cryoscanning EM (SEM), and cryo-transmission EM. We focused on the structure of the IMV particle, both after isolation and in the context of viral entry. For the latter, we used high-resolution cryo-SEM combined with cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 47 publications
5
46
2
Order By: Relevance
“…Analysis of all reconstructed particles in our tomograms supports the presence of two membranes, as postulated in recent studies (18,22,23). The outer viral membrane envelops the entire virion and presents a rough appearance on the outer side.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Analysis of all reconstructed particles in our tomograms supports the presence of two membranes, as postulated in recent studies (18,22,23). The outer viral membrane envelops the entire virion and presents a rough appearance on the outer side.…”
Section: Discussionsupporting
confidence: 52%
“…Other subsequent studies, such as those by Roos et al (21) and Griffiths et al (22,23), applied different sample preparation and visualization techniques, including immune labeling procedures (24). These contributions led to the proposal of models speculating on how subsequent assembly intermediates could be reflected in the final virion.…”
Section: Accinia Virus (Vv) Is the Best-characterized Member Of Thementioning
confidence: 99%
“…Initially, a single membrane was reported (Dales and Siminovitch, 1961), but the use of methods allowing better preservation of the ultrastructure led to publications claiming the existence in crescents of two closely apposed lipid bilayers (Sodeik et al, 1993). Subsequently, other studies supporting the presence in intermediate VACV particles of either one (Grimley et al, 1970;Morgan, 1976;Hollinshead et al, 1999;Heuser, 2005) or two (Griffiths et al, 2001a(Griffiths et al, , 2001bRisco et al, 2002) membranes have been published, leading to, at least, four different models to explain the evolution of membranes during VACV maturation (reviewed in Condit et al, 2006). One model involves the formation of single-membrane crescents which later enclose the DNA core which will not carry other membranes around it (Hollinshead et al, 1999).…”
mentioning
confidence: 99%
“…Furthermore, it has been suggested that the intracellular mature virion itself contains multiple membranes (15). The topological problems associated with the fusion of virions with multiple membranes have led to proposals of nonfusion mechanisms of entry (24).…”
mentioning
confidence: 99%